Pentingnya Konservasi Preventif Pada Benda-Benda Koleksi di Museum Kasunanan Keraton Surakarta - Made Prasta Yostitia Pradipta (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2024)
Surakarta Kasunanan Palace Museum is a private museum which contains the Palace's private collections. Many of them are now damaged, dusty, and even destroyed by age. Preventive conservation is used to prevent and minimize damage to museum collections. This research aims to discuss damage to museum collections and preventive conservation management that has been taking place at the Surakarta Kasunanan Palace Museum. Method used in this research is descriptive with kualitatif aproach method with interviews, observation and literature studies to collect data and use simple analysis. The results found that many collections in the Surakarta Kasunanan Palace Museum were unkempt and dusty. The preventive conservation carried out so far has only been less than optimal in terms of cleaning. The lack of available resources is also a factor in preventing preventive conservation efforts from running well.